Comparative meta‐analysis of Kabuki syndrome with and without hyperinsulinaemic hypoglycaemia. (15th July 2020) - Hoermann, Henrike; El‐Rifai, Omar; Schebek, Martin; Lodefalk, Maria; Brusgaard, Klaus; Bachmann, Nadine; Bergmann, Carsten; Roeper, Marcia; Welters, Alena; Salimi Dafsari, Roschan; Blankenstein, Oliver; Mayatepek, Ertan; et al.
Abstract: Background and Objective: Kabuki syndrome (KS), caused by pathogenic variants in KMT2D or KDM6A, is associated with hyperinsulinaemic hypoglycaemia (HH) in 0.3%‐4% of patients. We characterized the clinical, biochemical and molecular data of children with KS and HH compared to children with KS without HH in a multicentre meta‐analysis. Methods: Data of seven new and 17 already published children with KS and HH were compared to 373 recently published KS patients without HH regarding molecular and clinical characteristics. Results: Seven new patients were identified with seven different pathogenic variants in KDM6A (n = 4) or KMT2D (n = 3). All presented with HH on the first day of life and were responsive to diazoxide. KS was diagnosed between 9 months and 14 years of age. In the meta‐analysis, 24 KS patients with HH had a significantly higher frequency of variants in KDM6A compared to 373 KS patients without HH (50% vs 11.5%, P  < .001), and KDM6A ‐KS was more likely to be associated with HH than KMT2D ‐KS (21.8% vs. 3.5%, P  < .001). Sex distribution and other phenotypic features did not differ between KS with and without HH. Conclusion: The higher incidence of HH in KDM6A‐ KS compared to KMT2D‐ KS indicates that KDM6A loss of function variants predispose more specifically to beta cell dysfunction compared to KMT2D variants. As difficulties to assign syndromic characteristics to KS in early infancy often lead to delayed diagnosis, genetic testing for KS should be considered in children with HH, especially in the presence of other extrapancreatic/syndromic features.